0
$\begingroup$

I'm only studying for the final (during thanksgiving break no less :) )

I'm in PreCalc, and I've been struggling this entire semester. -.- So any help with studying would be really helpful

I find that I don't quite no where to proceed from here on this one.

The directions on this online study quiz are:

Solve the equation for the indicated variable:

$S = n(n+1)/6$ For "n"

I got as far as: $6*S/n+1 = n$, after performing the following steps:

Multiply on both sides by six.

Divide by $n + 1$

We get: $6*S/n+1 = n$

I know that I need to get that n in the denominator to the other side so I can presumably solve a quadratic but how??? I'm not asking for the answer, just what must I do to get past this step??

$\endgroup$
  • $\begingroup$ Multiply all the terms by $n$. $\endgroup$ – JB King Nov 27 '15 at 23:35
5
$\begingroup$

Instead of dividng by $n$, try this: \begin{equation*} \begin{aligned} S &= \frac{n(n + 1)}{6} \\ 6S &= n(n + 1) \\ 6S &= n^2 + n \\ 0 &= n^2 + n - 6S. \end{aligned} \end{equation*} So you are solving a quadratic equation in $n$. Try to finish from here.

$\endgroup$
  • $\begingroup$ OK give me a few minutes I will try your suggestions! $\endgroup$ – MegaWitt Nov 27 '15 at 23:44
  • $\begingroup$ I should have mentioned there are ten questions on this study quiz, I want to know if I'm on the right track before I continue on. I used the quadratic formula: $-1+sqrt(1-4(6*S))/2$ Multiplied by the conjugate: $(-1+sqrt(1-24*S)/2) * -1+sqrt(1-24*S)/-1+sqrt(1-24*S)$ and this is just getting way too difficult I must be doing something wrong :( $\endgroup$ – MegaWitt Nov 27 '15 at 23:56
  • $\begingroup$ I don't see why you would "multiply by the conjugate." The quadratic formula already is the answer. But you must apply it accurately: the constant term is $-6S$, not $6S$, so you end up with $\frac12(-1 \pm \sqrt{1+24S})$. $\endgroup$ – David K Nov 28 '15 at 0:28
1
$\begingroup$

Hint 1: Using the distributive law, $$(x+a)(x+b) = x^2+Ax+B$$ express $A$ and $B$ in terms of $a$ and $b$ (e.g. $B=ab$, what does $A=$?). Use this model to solve $n^2+n-6S=0$.

Hint 2

Complete the square $$\begin{array}{lll} n^2+n-6S&=&0\\ 4n^2+4n-24S&=&0\\ 4n^2+4n&=&24S\\ (2n)^2+2(2n)&=&24S\\ (2n)^2+2(2n)+c&=&24S+c\\ \end{array}$$ What would $c$ have to be in order to make a perfect square (hint 2a: suppose $m=2n$)

Hint 3

derive the quadratic formula from $ax^2+bx+c=0$ by completing the square $$\begin{array}{lll} ax^2+bx+c&=&0\\ 4a(ax^2+bx+c)&=&4a(0)\\ 4a^2x^2+4abx+4ac&=&0\\ 4a^2x^2+4abx&=&-4ac\\ (2ax)^2+2b(2ax)&=&-4ac\\ (2ax)^2+2b(2ax)+d&=&d-4ac\\ \end{array}$$ for what value of $d$ would make the Left-hand-side a perfect square (suppose that $z=2ax$)? Use these results to solve the problem.

$\endgroup$
  • 1
    $\begingroup$ Are there mistakes/typo's in this? Where is the "m" in $m = 2n$?? Or is that the general form for completing the square? In which case I've never seen that, just examples. I see that you multiplied by four in the second step of hint 2. Is that because you took half the coefficient of the b term squared that giving you 1/4th and then multiplied the entire equation by four to eliminate the denominator?? And jesus. The italics are really throwing me off :P $\endgroup$ – MegaWitt Nov 29 '15 at 12:15
  • $\begingroup$ We multiply by four because we would like the middle coefficient to be even, and the leading coefficient to be a perfect square. The goal of eliminating fractions until the last step makes this necessary because we do not know whether $n$ is even or odd. $\endgroup$ – John Joy Nov 29 '15 at 14:17
  • $\begingroup$ What happens to the equation $(2n)^2+2(2n)+c=24S+c$ when we substitute $m$ for every occurrence of $2n$? Ans. the equation becomes $m^2+2m+c=24S+c$, which has a quadratic on the LHS with no leading coefficient. What value of $c$ would make this a perfect square. $\endgroup$ – John Joy Nov 29 '15 at 14:21
  • $\begingroup$ OK in case you saw that last comment I am sorry about that, this site has not been nice to me a few times and I was under the impression you were attempting to mess me up. That italic text is really confusing, and so too is the way you wrote it out. I get it though. Its more helpful from a certain perspective. I'm sure the answer is $2*root(6) -1/2 = n$ $\endgroup$ – MegaWitt Dec 9 '15 at 1:11
  • 1
    $\begingroup$ Continuing from Hint 2, obviously, $c=1$ $$(2n)^2+2(2n)+1^2=24S+1$$ $$(2n+1)^2 = 24S+1$$ $$2n+1 = \pm\sqrt{24S+1}$$ $$n=\frac{-1\pm\sqrt{24S+1}}{2}$$ $\endgroup$ – John Joy Dec 9 '15 at 14:43
0
$\begingroup$

Hint:

It is equivalent to the quadratic equation in $n$: $$n^2+n-6S=0.$$

$\endgroup$
  • $\begingroup$ I don't follow you. What is your unknown? $\endgroup$ – Bernard Nov 27 '15 at 23:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.